Cellulose Nanofibers from Regenerated Cellulose fibers of Cigarette Butts and Application in Pickering Emulsion - Amanda, Putri; Masruchin, Nanang; Amelia, Anita (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2022)
Cellulose nanofibers (CNF) have been applied in various applications due to the abundant raw materials and excellent mechanical and thermal properties. In this work, CNF from Cigarette butts (CNF-CB) was used as emulsion stabilized for oil in water emulsion. CNF was prepared from regenerated cellulose fibers that were produced by deacetylation of Cigarette butts waste using autoclave and then hydrolysis by chemical treatment using sulfuric acid. The FTIR spectra of CNF-CB showed chemically convert from Cigarette butts waste, indicating removal of the acetyl group. TEM micrographs showed nanocellulose with diameters of 8-32.30 nm. XRD analysis shows that the CNF-CB is a cellulose II allomorph with a crystallinity index of about 88.04%. Thermogravimetric analysis showed high char residue for the nanocellulose compared to raw fibers. The addition of CNF-CB with a concentration of 0.5% into the oil-in-water emulsion (O/W) showed better stability than commercial surfactant. In conclusion, this approach offers a promising strategy for upcycling cigarette butts waste to produce nanocellulose, which could be used in various applications.